Research and practice on the infrastructure for operator industry digitalization platform - ZHENG Xiang; DU Baolan (Dianxin kexue)
With the upgrading of China's digital strategy, various industries have gradually entered the deep water of digital transformation. Focusing on the "industrial digitalization platform infrastructure" as the research area and aiming at the "digital transformation of operator industry" ,the current situation and future development trends of digital transformation in the operator industry during the digital era were reviewed. And starting from the actual situation of telecom operators, the current situation and practical shortcomings of the industrial digitalization platforms were analyzed, and the expectations for the practical innovation of the operator industry digitalization platform in the future were proposed.